mTOR regulates MAPKAPK2 translation to control the senescence-associated secretory phenotype - Herranz,N; Gallage,S; Mellone,M; Wuestefeld,T; Klotz,S; Hanley,CJ; Raguz,S; Acosta,JC; Innes,AJ; Banito,A; Georgilis,A; Montoya,A; et al. (Nature Cell Biology, 2015)
Senescent cells secrete a combination of factors collectively known as the senescence-associated secretory phenotype (SASP). The SASP reinforces senescence and activates an immune surveillance response, but it can also show pro-tumorigenic properties and contribute to age-related pathologies. In a drug screen to find new SASP regulators, we uncovered the mTOR inhibitor rapamycin as a potent SASP suppressor. Here we report a mechanism by which mTOR controls the SASP by differentially regulating the translation of the MK2 (also known as MAPKAPK2) kinase through 4EBP1. In turn, MAPKAPK2 phosphorylates the RNA-binding protein ZFP36L1 during senescence, inhibiting its ability to degrade the transcripts of numerous SASP components. Consequently, mTOR inhibition or constitutive activation of ZFP36L1 impairs the non-cell-autonomous effects of senescent cells in both tumour-suppressive and tumour-promoting contexts. Altogether, our results place regulation of the SASP as a key mechanism by which mTOR could influence cancer, age-related diseases and immune responses.